Functional Divergence of Two Zebrafish Midkine Growth Factors Following Fish-Specific Gene Duplication - Winkler, Christoph; Schäfer, Matthias; Duschl, Jutta; Schartl, Manfred; Volff, Jean-Nicolas

(untitled) (Genome Research, 2003)
In mammals, the unique midkine (mdk) gene encodes a secreted heparin-binding growth factor with neurotrophic activity. Here, we show the presence of two functional mdk genes named mdka and mdkb in zebrafish and rainbow trout. Both midkine proteins are clearly different from the related pleiotrophin, which was also identified in zebrafish and other fishes. Zebrafish mdka and mdkb genes map to linkage groups LG7 and LG25, respectively, both presenting synteny to human chromosome 11, in which the unique human ortholog mdk is located. At least four other genes unique in mammals are also present as duplicates on LG7 and LG25. Phylogenetic and divergence analyses suggested that LG7/LG25 paralogs including mdka and mdkb have been formed at approximately the same time, early during the evolution of the fish lineage. Hence, zebrafish and rainbow trout mdka and mdkb might have been generated by an ancient block duplication, and might be remnants of the proposed fish-specific whole-genome duplication. In contrast to the ubiquitous expression of their mammalian counterpart, zebrafish mdka and mdkb are expressed in spatially restricted, mostly nonoverlapping patterns during embryonic development and strongly in distinct domains in the adult brain. Ectopic ubiquitous expression of both mdk genes in early zebrafish embryos caused completely distinct effects on neural crest and floorplate development. These data indicate that mdka and mdkb underwent functional divergence after duplication. This provides an outstanding model to analyze the molecular mechanisms that lead to differences in pathways regulating the formation of homologous embryonic structures in different vertebrates.